Subliminal Training Techniques for Cognitive, Emotional and Behavioural Balance. The role of Emerging Technologies - Drigas, Athanasios; Mitsea, Eleni; Skianis, Charalampos (Technium Social Sciences Journal, 2022)
Traditionally, metacognition & higher mental abilities are thought to be exclusively linked to consciousness. However, a growing number of researchers support the idea that nonconscious processes may hold the keys to higher forms of intelligence. Subliminal messages expose individuals to visual or/and auditory stimuli below the threshold of perception. The current review aims to explore the effectiveness of subliminal cues on fundamental aspects of metacognition such as higher cognitive and emotional meta-abilities, affective and behavioral regulation, and academic achievement. In this context, we search for and classify the existing subliminal training techniques, while evaluating the usability of ICTs such as virtual reality, mobile apps, intelligent tutoring systems, and software in subliminal learning and training. The results of this review revealed that subliminal techniques improve all those aspects that assure metacognitive improvements in terms of self- & emotional regulation, higher mental abilities, and behavioral modification. Subliminal cues lower people’s shields and update filtering mechanisms enabling people to focus on positive rather than negative interpretations. Subliminal techniques are under the umbrella of metacognitive strategies, since they can used consciously to increase self-regulation capacity as wells as expand the horizons of consciousness. Subliminal teaching techniques can be used by teachers and parents in general and special education to instill higher-level needs & motives, accelerate students’ performance and unfold students’ existing but underdeveloped abilities. Therapists can also utilize these methods to help patients with phobia, anxiety and depression to overcome fear. Subliminal techniques can be also used as a strategy by leaders, mentors, and employees to build trust, inspire and provide humanity with innovative ideas. ICTs provide the ideal environment for implementing subliminal training. However, more research is needed.